TEORI PRODUCT LIFE CYCLE : SUATU ALAT UNTUK FORMULASI STRATEGICAL ALIGNMENT - Abd. Hamid Habbe (Media Riset Akuntansi, Auditing & Informasi, 2002)
The theory of Product Life Cycle (PLC) can be used as a guide or instrument to formulate and implement a strategy that fits the business environment based on phase analysis of deterministic characteristics in PLC. The organization strategy chosen by a company can be changed according to the environment change. The paper argues that organization strategy selection is an ongoing process.Keywords: Product life cycle, Organization strategy, Changes.